CRISPR/Cas Powered Multiplexed Biosensing. Issue 8 (August 2019) - Bruch, Richard; Urban, Gerald A.; Dincer, Can
Abstract : Multiplexed CRISPR/Cas biosensing offers various possibilities for diagnosing different diseases by analyzing many analytes from one single specimen. However, in this relatively new field, nearly no multiplexing approaches exist, as many challenges need to be addressed. We discuss the reasons behind it and possible strategies to push the multiplexing level.